Exploring medical interns' knowledge on hypertension - Margarita Rosa Roméu Escobar; Luis Padrón Velázquez; Beatriz Sabina Roméu; Zulema Bos Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: hypertension is one of the greatest challenges of modern medicine. It is still unknown how well prepared are the medical interns to address this significant health issue. Objective: to explore knowledge acquired by sixth year students of medicine on "Cuban guidelines for the prevention, diagnosis and treatment of hypertension" and to evaluate the results of medical licensing examinations according to this condition. Methods: a descriptive research conducted at the University of Medical Sciences of Cienfuegos from October 2009 to February 2010. A screening test was applied to 34% of the medical interns and the agenda of 2007-2008 and 2008-2009 medical licensing examinations was reviewed. Results: 73.4% of the medical interns passed the screening test. The percentage of students who made mistakes in different aspects was identified as follows: 53.3% when measuring blood pressure, 64% when deciding a treatment according to cardiovascular risk stratification, 62.6% on lifestyle changes and 52% on drugs identification. In the 2007-08 medical licensing examinations a question was posed on hypertension and in 2008-09 an item was included. 53.1% of the interns made mistakes in 2007-08's question and 43% in 2008-2009's. Conclusions: the interns that participated in the investigation showed weaknesses in the essential learning on hypertension. On medical licensing examinations for medicine students the issue is not as fully and deeply addressed as its relevance requires.